CURRENT PRACTICE OF USING SPECIALIZED KNOWLEDGE IN THE INVESTIGATION OF CRIMES INVOLVING CAUSING BODILY HARM (TSUL LEGAL REPORT, 2026)
This article explores the use of specialized knowledge in investigating crimes involving bodily harm, highlighting its essential role in achieving just and effective outcomes. The study focuses on the application of forensic medical examination, criminalistic methods, and other specialized fields within the investigative framework. The topic’s significance is driven by the high prevalence of bodily harm cases in crime statistics, with expert opinions playing a pivotal role in ensuring fairness and precision in investigations. The article aims to assess the effectiveness of specialized knowledge, pinpoint existing challenges, and propose ways to expand its application in investigative practice. The research employs a methodology that includes legal analysis, a thorough literature review, empirical observations from investigative practices, and insights from expert opinions. The findings provide practical and scientific insights to optimize law enforcement operations, enhance investigation quality, and strengthen the reliability of expert conclusions, contributing to a more equitable and robust criminal justice system.